Isolation, characterization, therapeutic and prophylactic applications of a lytic bacteriophage to combat multi-drug resistance Shigella flexneri: an animal study model - Abbasi Fashami, Parisa; Pournajaf, Abazar; Amirmozafari, Nour; Hallajzadeh, Masoume; Mahabadi, Vahid Pirhajati; Saghiri, Reza; Khafri, Soraya; Golmoradi Zadeh, Rezvan; Akrami, Sousan; Asgharzadeh, Sajjad; Rajabnia, Mehdi (GMS Hygiene and Infection Control)
Background: Shigella (S.) flexneri is one of the most important causes of disease in children with diarrhea in Iran. Today, bacteriophages are an attractive option to resolve the drug resistance problem among pathogenic agents. Accordingly, the present study aimed to isolate a lytic bacteriophage of S. flexneri and investigate its impact on reducing excretion of Shigella in mouse models suffering from bacillary dysentery. Method: S. flexneri ATCC12022 was used. Identification of the phage isolated from hospital wastewater was performed using Transmission Electron Microscopy (TEM). Stability tests were performed to determine the sensitivity of isolated phages to various factors such as temperature, pH and bile salts. A male Syrian mouse model (C57), with mice 6 weeks of age weighing 22–25 g, was used to ensure safety and efficacy of the bacteriophage in reducing Shigella in stool. Treatment with the phage was performed (I) 1 h before, (II) 1 h after, (III) 5 h after, and (IV) 1 h before +1 h after bacterial challenge. Results: TEM indicated that the bacteriophage used in this study belongs to the Myoviridae family. Administration of one dose of bacteriophage before the infection can accelerate improvement post-transfection, and administration of bacteriophage post-infection has a therapeutic influence. Conclusion: In vivo and in vitro results indicate that our bacteriophage causes complete lysis of S. flexneri. Thus, this phage could be a therapeutic option for treating bacillary dysentery resulting from multidrug-resistant S. flexneri.